MODERN UKRAINIAN ZEMSTVO STUDIES AS A COMPONENT OF LOCAL HISTORICAL STUDIES (Південний архів (історичні науки), 2024)
The main purpose of article is to examine the contribution of research on the history of regional zemstvos to the development of modern Ukrainian local history. One of the directions of historical regional studies is the study of the history of certain organizations and institutions of the region, as well as the life and work of prominent countrymen. It is no secret that one of the institutions that did a lot for the development of certain regions of Ukraine at the turn of the 19th and 20th centuries were the zemstvo self-government bodies, introduced as a result of the Zemstvo reform of 1864. These were the first elected all-state bodies on the territory of the empire, which made it possible to involve interested representatives of society, including nationally conscious intelligentsia, in solving the problems of social and economic development of the province. After Ukraine gained independence, interest in the history of its individual regions and the history of the constituent elements of these regions increased. Including the increasing number of works dedicated to the history of regional zemstvos and, therefore, the history of socio-economic development of a certain area. The relevance of this topic is due to the desire to focus on the importance of regional zemstvo research specifically for local studies and the almost complete absence of historiographic research on this topic. On the basis of general scientific methods of analysis and synthesis, the importance of regional zemstvo studies for local studies is proven. Results. The authors of the study analyzed how research on the history of individual zemstvos provides material for the development of modern local history. Special attention is paid to studies devoted to the history of the practical activity of zemstvos, because they made available to scientists’ huge strata of archival unknown or little-known sources from the history of the region. Also, attention was paid to the importance of researching the history of the activities of prominent Zemstvos as representatives of the public of the region and exponents of public opinion. It has been analyzed which Ukrainian provinces have most recently come into the field of view of researchers of the history of the zemstvo. Conclusions were made that the history of zemstvo self-government of different provinces of Ukraine was a source for obtaining a huge layer of local history material of the XIX–XX centuries. In general, the era of independence became a favorable stage both for the study of the history of individual zemstvos of Ukraine and for the development of historical regional studies as such, which in general brought Ukrainian historical science closer to the creation of a coherent, objective picture of Ukrainian history.
Keywords: local lore, local self-government, zemstvo, historiography, regionalism, zemstvo activity, provincial zemstvo.